Redescription of males of the aphid species Cinara (Cupressobium) tujafilina and Cinara (Cupressobium) cupressi (Hemiptera, Lachninae) - Durak, Roma; Durak, Tomasz (Zootaxa, 2015)
This paper presents the first comprehensive description of the winged males of Cinara tujafilina and Cinara cupressi (Hemiptera, Lachninae) and establishes the morphological characters enabling differentiation between them. We show that some populations of C. tujafilina, a species considered to be anholocyclic, may not have lost the genetic ability to produce males and under favourable conditions can develop in a holocyclic manner.